The metabolic ability of swallowtails results in the production of bioactive substances from plant components. - Miho Nakano; Takuma Sakamoto; Yoshiyuki Itoh; Yoshikazu Kitano; Kaori Tsukakoshi; Hidemasa Bono; Hiroko Tabunoki (PLoS ONE)
Host plant selection may depend on the metabolic system in herbivorous insects. Although oligophagous insects take up specific host plant components, how host plant components and their biological activities are altered through their metabolic systems remains unknown. Here, by examining gene expression of metabolic enzymes and components in the larval frass, we investigated the metabolic ability of Papilio memnon larvae fed with Citrus x paradisi (grapefruit) against host plant components. The gene expression levels of some metabolic enzymes were fluctuated between the larval midgut and the larval fat bodies. Furthermore, the chloroform extract from the larval frass, but not that from grapefruit leaves, inhibited cell viability of human pancreatic cancer cell line, MIA PaCa2. Finally, we identified two chlorophyll catabolites, pheophorbide-a and pyropheophorbide-a, in the larval frass extract. Pyropheophorbide-a reduces cell viability of and induces morphological changes in cells of MIA PaCa2; in addition, pheophorbide-a and pyropheophorbide-a inhibit the aggregation of amyloid β-protein (human, 1-42). Therefore, the chemical structure and biological activity of host plant components are affected by the P. memnon metabolic system. Our findings may contribute to the understanding of the process for producing pheophorbide-a and pyrophephorbide-a from chlorophyll, facilitated by the metabolic ability of P. memnon larvae.